Perancangan Media Pembelajaran Interaktif pada Mata Pelajaran Ilmu Pengetahuan Alam Berbasis Android Kelas VIII di SMP Negeri 9 Pariaman - Sari, Nike Furnike; Supriadi, Supriadi (Indonesian Research Journal on Education, 2022)
This research was motivated by several problems such as the implementation of teacher learning more delivering material with the lecture method, science learning media in class VIII SMP Negeri 9Pariaman not yet using Android-based interactive learning media which contains science material. The learning media used by the teacher is less varied, the media used previously was Power Point. The purpose of this research is to design interactive learning media for natural science subjects based on Android class VIII at SMP Negeri 9 Pariaman that are valid, practical and effective. The research method used in this study is the Research And Development (R&D) method using the 4D version approach, namely Define, Design, Develop and Disseminate. Luther Sutopo's version of the multimedia development model which consists of six stages, namely concept, design, material collecting, assembly,testing and distribution, the product test used in this study is a validity test, namely content, construct and language using the Aiken's V formula. Practicality test by the teacher science subjects using the Moment Kappa formula and the effectiveness test by students using the N-Gain formula. The results of the study of science learning media used by teachers and students in science subjects. The form of this learning media is in the form of an Android-based apk that can be used on students' Android smartphones. Meanwhile, for the product validity test of 0.87 which was declared valid, the results of the practicality test of 0.83 which were stated to be very practical and the results of the effectivenesstest of 0.84 which were declared effective. So it can be concluded that the Android-based sciencelearning media as a learning medium is valid, practical and effective.